MECHANICAL ANALYSIS ON HEAVY DUTY ROLLER - Adzan Jati Prasetyo; Sri Nugroho; Rifky Ismail (JURNAL TEKNIK MESIN, 2024)
Mechanical analysis is a critical aspect of engineering that aims to understand the root causes of component failures and develop strategies to prevent future occurrences. This thesis presents a comprehensive failure analysis of heavy-duty rollers used in industrial applications, focusing on identifying the mechanisms that lead to their premature failure. Heavy-duty rollers are subjected to extreme operational conditions, including high loads, varying speeds, and harsh environmental factors, making them prone to wear and failure. The study involved a detailed examination of failed roller samples using various analytical techniques, including visual inspection, metallurgical analysis, scanning electron microscopy (SEM). The results revealed that the primary failure mechanisms were fatigue, abrasive wear, and improper lubrication. Fatigue failures were characterized by the presence of micro-cracks that propagated over time due to cyclic loading. Abrasive wear was identified through the examination of surface topography, indicating that particles entrapped between rolling surfaces led to significant material removal. Additionally, improper lubrication was found to exacerbate both fatigue and wear by increasing friction and thermal stresses. The analysis also highlighted several contributing factors to these failure mechanisms, such as material defects, manufacturing inconsistencies, and inadequate maintenance practices. Metallurgical analysis indicated the presence of non-metallic inclusions and improper heat treatment as significant factors compromising the material integrity. These include material selection enhancements, optimized heat treatment processes, improved lubrication strategies, and rigorous maintenance protocols. Implementing these recommendations is expected to significantly reduce the failure rate and extend the operational lifespan of heavy-duty rollers in industrial settings. This study underscores the importance of a systematic approach to failure analysis and provides a framework for addressing similar issues in other critical components. The insights gained from this research contribute to the broader field of reliability engineering and have practical implications for industries relying on heavy-duty roller systems.